Development of Pre-consolidation Pressure Dependence of Mixed Hardening Multisurface Hyperplasticity Model for Better Prediction of Earthquakes Ground Response Analysis - Dedi Apriadi; Halida Yunita; Suched Likitlersuang; Thirapong Pipatpongsa (Institut Teknologi Bandung, 2011)
Abstract. It was known that soil behavior is dependent upon the history of loading and exhibits hardening behavior when deformed plastically. This paper presents a formulation of mixed hardening multisurface hyperplasticity model with stiffness factors of the kinematic hardening of the yield surfaces proportional to the pre-consolidation pressure to represent the history of loading. Formulation is emphasized for describing the cyclic loading behavior of clay soils. The advantages of this approach are that it can reproduce smooth transitions from elastic to plastic behavior and allows the stress-reversal history to be memorized by the internal variable function. The Modified Cam Clay yield function is selected as a key model to simulate the stress-strain response. The incremental stress